Evaluasi Unjuk Kerja Low Pressure Heater PLTU PT.X - Hernawan Novianto (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2022)
Efficient use of energy is a top priority in the oil and gas industry, the aim is to reduce operational costs, one of these efforts can be done by utilizing the heat from the process to heat the feed before it is heated in the furnace, as is the case with heat exchangers. The effectiveness of the heat exchanger indicates the performance of the heat exchange process in the heat exchanger, both by convection and conduction. Over time, the effectiveness of the heat exchanger will decrease due to fouling formed and other things that can reduce the effectiveness of the heat exchanger. Through the performance evaluation, the performance of the heat exchanger can be indicated which can be used for future maintenance and repair plans. Thermal effectiveness was calculated using the dirt factor and pressure drop methods, and the calculated operating fouling factor was 0.002 Btu.ft2.°F /hr, this condition exceeded the maximum allowable design limit of 0.005 Btu.ft2.°F/hr, while the calculated pressure drop is 2,72 psi. This condition is still below the maximum allowable design limit of 10 psi, so this heat exchanger is still feasible to use. Calculation of the effectiveness of the heat exchanger results in an effectiveness of 34,075%.